Psychometric Properties of a Self-Report Instrument for the Assessment of Tic Severity in Adults With Tic Disorders. Issue 6 (November 2015) - Abramovitch, Amitai; Reese, Hannah; Woods, Douglas W.; Peterson, Alan; Deckersbach, Thilo; Piacentini, John; Scahill, Lawrence; Wilhelm, Sabine
Abstract: The gold-standard measure of tic severity in tic disorders (TD), the Yale Global Tic Severity Scale (YGTSS), is a semistructured clinician-administered interview that can be time consuming and requires highly trained interviewers. Moreover, the YGTSS does not provide information regarding frequency and intensity of specific tics because all motor and all vocal tics are rated as a group. The aim of the present study is to describe and test the Adult Tic Questionnaire (ATQ), a measure for the assessment of tic severity in adults, and to report its preliminary psychometric properties. The ATQ is a brief self-report questionnaire that provides information regarding frequency, intensity, and severity of 27 specific tics. In addition, the ATQ produces total frequency, intensity, and severity scores for vocal and motor tics, as well as a global total tic severity score. Results showed that the ATQ demonstrated very good internal consistency and temporal stability. The total, vocal, and motor tic severity scales of the ATQ showed strong correlation with corresponding subscales of the YGTSS, indicating strong convergent validity. Weak correlations with measures of severity of obsessive-compulsive disorder and attention deficit/hyperactivity disorder, indicated strong discriminant validity. The ATQ, a promising measure for the assessment of tic severity in adults with TD, may be a valuable supplement to the current recommended assessment battery for TD. Furthermore, the ATQ enables clinicians and researchers to track changes in the frequency and intensity of specific tics, which is important given their complex and dynamic nature. Highlights: We describe the development of the ATQ, a multidimensional measure of tic severity in adults The ATQ is a brief self-report measure that provides both global and detailed tic-specific scores The ATQ demonstrates strong psychometric properties The ATQ may be particularly useful for assessing treatment progress in research and clinical settings